PENGARUH KEPEMIMPINAN KEPALA SEKOLAH TERHADAP DISIPLIN GURU SDN 023 PANDAU JAYA KABUPATEN KAMPAR KECAMATAN SIAK HULU KELURAHAN PANDAU JAYA - Maulida '; Gimin '; Hardisem Syabrus (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstak: the leadrsdhip is the ability to influennce, give the directive and motivate a group of members in order to work reaching of the goal and the goal objective in thus research is to find out how big the influenced of leadership of the head master about diciplined teacher. Head master is that they are a lot of knowing the tasks and they determine rhythm for their school’s like give motivation and direction. The diciplined is an attitude, action and thomselves control someone or a group mustbe follow the rules that have been set to embodu the goal of the organization maximum. The respondent’s in this reaserch was all over teacher SDN 023 Pandau Jaya that amounts to 30 person. Collecting teaching data in this research using the inquires with the scale likert, engineering analysis data using analysis descriptive SPSS ersion 0.21. analysis result variabel depemdemt (teacher diciplined) influence by variabel independent (teacher diciplined, give directives, motivation teacher) of 23,3% while the rest of 76,7% influenced by other not included in this research.Key word : Leadership, Diciplined Teacher, Headmastres.